Bioactivity and chemical composition of Penicillium griseofulvum from estuarine soil in East Java, Indonesia - AFRIAN ROSYADI; MOCHAMAD RAZAQ SETYANTO; BAWON TRIATMOKO; JOKO TRI WIBOWO; LESTYO WULANDARI; EVI UMAYAH ULFA; ARI SATIA NUGRAHA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rosyadi A, Setyanto MR, Triatmoko B, Wibowo JT, Wulandari L, Ulfa EU, Nugraha AS. 2025. Bioactivity and chemical composition of Penicillium griseofulvum from estuarine soil in East Java, Indonesia. Biodiversitas 26: 3745-3757. Fungi have been a notable source for new antibiotic discovery, yet bioprospecting on Indonesian micro fungi remains scarce. The previous study has collected several soil fungi from understudied estuarine areas, a unique environment where the coastal region has provided a fertile environment for fungi to grow and adapt. This has left the soil fungi as a promising source of antibacterial compounds. This study aimed to isolate antibiotic-producing fungi from these unique estuarine habitats as well as evaluate their secondary metabolite. Soil samples were collected from Kendit Village, Situbondo, East Java, Indonesia. Antibacterial activities were measured based on the CLSI microdilution method. Species identification of fungi was based on the DNA barcoding technique using ITS region-specific primers. A secondary metabolite was produced using solid-state fermentation using rice as substrate. Metabolite profiling relied on the GC-MS technique. Seven fungal isolates were obtained and tested for antibacterial activity against Staphylococcus aureus. All isolates exhibited positive inhibition, with isolate IS-IB-T2 showing the highest activity, forming an inhibition zone of 18.37?±?0.31?mm. IS-IB-T2 was identified as Penicillium griseofulvum isolate CF00049 (GenBank accession no. OQ076449.1). It demonstrated significant antibacterial activity against S. aureus (30.5?±?3.9% inhibition) and Pseudomonas aeruginosa (65.6?±?3.1% inhibition). GC-MS analysis revealed 18 bioactive compounds, with n-Hexadecanoic acid, Hexadecanoic acid ethyl ester, and Vinyl trans-cinnamate as major constituents. These compounds are known to disrupt bacterial metabolic processes, redox balance, and membrane integrity. In summary, the study suggested that the estuarine habitat was a notable source for antibiotic-producing fungal isolates. Isolated P. griseofulvum from the Situbondo estuarine environments holds potential as a natural source for the development of new antimicrobial agents. Further research is necessary to isolate the bioactive compound as well as obtain the Minimum Inhibitory Concentration (MIC) value of the single compound.